Competitive dynamics, IP litigation and acquisitions: The struggle for positional advantage in the emerging mobile internet - Timo Seppälä; Martin Kenney (The Research Institute of the Finnish Economy (ETLA), 2012)
This article investigates how current global intellectual property (IP) litigation provides insight into the competitive landscape of mobile internet, the strategic thinking processes of firms, and the old mobile telecommunications incumbents and new entrants from internet that are vying for space in the new world of mobile internet. To understand the contemporary industry of smart devices, we used the latest IP litigation data from the U.S. to illustrate how the world of essential patents (i.e., the old incumbents in mobile telecommunications) and the world of platform patents (i.e., the new entrants into mobile internet) have become two complementary areas of technology. This analysis addresses the necessity for understanding the firms involved in IP litigation cases for smart devices in particular and the corresponding patents these firms use in current global IP litigation. This article provides evidence that elucidates the current turmoil in mobile telecommunications; identifies the valuable patents, corresponding patent categories and technology areas; and discusses and analyzes the competitive landscape of mobile internet through the eyes of IP litigation and IP acquisitions. Furthermore, we provide additional evidence that the patent acquisitions by Apple, Google, and Microsoft changed the nature of their ownership of different technologies and important patents in the world of essential patents.
Keywords: K4; K41; L25; L8; L86; 330; Apple; Google; Microsoft; Nokia; ICT; Intellectual Property (IP); IP Litigation; IP Acquisitions